Pedagogy for Sustainable Development among Geography Teachers Towards Implementing Sustainable Developmnet Goals (SDGs) - Mohd Zaki Said; Mohammad Zohir Ahmad (Jurnal Pendidikan Geosfer, 2021)
Pedagogy for sustainable development is important towards implementing the Sustainable Development Goals (SDGs) in education including the Geography curriculum in Malaysia. The purpose of this study was to measure frequency uses of Pedagogy for Sustainable Development approaches among Geography teachers. This study used a quantitative approach by utilizing a questionnaire involving 252 samples of Geography teachers in Penang, Malaysia. The finding showed a high level of frequency in the use of storytelling approach (M=4.00, SD=0.771), an emphasis on sustainable living (M=4.12, SD=0.683), cultivating a sense of appreciation for living things and nature (M=4.40, SD=0.621) and promoting values (M=4.28, SD=0.680). Teachers like to implement the teacher-oriented learning-based activities through the approach of promoting, nurturing and emphasizing the issues of Sustainable Development (SD). Geography teachers prefer to implement the teacher-oriented learning-based activities compared to student-based learning issues. The findings revealed that the experiential learning technique are at high  frequency level of use compared to the real-world learning method and critical problem-solving learning. As a result, the study indicated that the Pedagogical of Sustainable Development approach has not yet received high attention from Geography teachers to be used (to use) in class as a teaching approach as global requirement in educating students about SDGs Agenda.